Mabel Fitzhugh - San Jose State College:::::::::
Mabel Fitzhugh, shown here with department head Margaret Twombly as faculty in the Health and Hygiene department, traveled the country to work with polio patients and share her expertise. (San Jose State La Torre, 1944)